(untitled) (Journal of Forestry, 2024)
In forestry, measurements are made to understand the state of natural ecosystems and their changes. The studies have reported that geographical features such as elevation, slope and aspect affect the ecosystem dramatically and that it is crucial to measure them accurately. Also, in forestry analysis and risk assessments, these features are required to be scored objectively and accurately. Elevation and slope can be easily measured and scored using GISbased systems. Although the aspect can be measured simply, the studies suggested diverse approaches on scoring it. The reason for this diversity is essentially that the studies determine the aspect visually and that the circular structure of the aspect makes the scoring difficult. Also, the score of the aspect value differs according to the study hemisphere and concept. Therefore, the requirement of an objective and easily applicable GIS-based measurement and scoring method of the aspect is genuine. In the study, Maçka Forestry Enterprise, which is located in the Trabzon province of Türkiye, was chosen and the aspect map of the region was obtained. Then, 30 forest roads and 30 landslide areas were selected from the region. The forest roads and landslide areas were evaluated according to their aspect, visually. These visual assessments were scored according to the studies in the literature. After all, the aspect scores of the forest roads and landslide areas were also determined according to the proposed method. This method suggests scoring the aspect in a pixel-wise manner and circular averaging. The results were compared and have shown that the aspect scoring studies in the literature are subjective and contradict each other in many ways. The results also showed that the proposed method is accurate, objective, and effective in measuring and scoring the aspect. Also, the proposed method provides a virtual approach rather than a visual one. Finally, the proposed method is shared as an open-source ArcMap Toolbox to be delivered to the end-user.